Synthesis and Crystal Structure of Chiral (1R,5R)-3-Arylidenopinones - Yang, Yi-Qin; Xu, Hai-Jun; Lan, Lan; Wang, Shi-Fa (Asian Journal of Chemistry, 2013)
Three (1R,5R)-(-)3-arylideneopinones (2a, 2b and 2c) were first synthesized and characterized by IR, MS, NMR, elemental analysis and single-crystal X-ray diffraction method. The structure indicates that the compound 2a belongs to orthorhombic, space group P212121 with a = 1.0378 (5) nm, b = 1.1156 (6) nm, c = 1.2775 (7) nm, b = 90º. V = 1.4791 (13) nm3, Z = 4, r = 1.223 g cm-3, μ = 0.083 mm-1, F (000) = 584 and final R1 = 0.0327, wR2 = 0.0876. The compound 2b belongs to trigonal, space group P32 with a = 0.93024(12) nm, b = 0.93024(12) nm, c = 1.3215(4) nm, b = 90.0º. V = 0.9903(3) nm3, Z = 3, r = 1.219 g cm-3, μ = 0.079 mm-1, F(000) = 390 and final R1 = 0.0350, wR2 = 0.0912. The compound 2c belongs to monoclinic, space group P21 with a = 1.20252 (15) nm, b = 0.99228(12) nm, c = 2.3905(3) nm, b = 92.769(2)º. V = 2.8491(6) nm3, Z = 8, r = 1.216 g cm-3, μ = 0.254 mm-1, F(000) = 1104 and final R1 =0.0440, wR2 = 0.1069.